Diversity in unity – Voices from the past, the focus on Belhar and the on-going quest for unity - Botha, Johan (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
This contribution focuses on the on-going ecclesiological quest by the Dutch Reformed Church (DRC) family to become a visible, living and practicing diversity in unity. It highlights remarkably clear and foundational theological contributions with regard to this matter, by trustworthy voices from inside (e.g. individuals like Botha, Durand, Jonker as well as by several church meetings and synods) and outside (e.g. theologians like J Calvin and K Barth) the DRC Family, in opposition to wrong ecclesiological convictions and practice. In relation to this the core focus of the confession of Belhar on the church as visible and as diversity in unity, is emphasised as foundational to the character of the church of Christ. Guiding perspectives on this fundamental truth are also drawn from important contributions by Dirkie Smit, in particular from his thoughts on the ecclesiology in the confession of Belhar.